Development of a Quizizz-Based Cognitive Diagnostic Assessment Instrument for the IPAS Subject of Grade IV of SD Negeri 2 Ciloa - Mayanesa , Ulmi Reda; Sutisna, Atang (Universitas Nusantara PGRI Kediri, 2025)
The lack of use of interactive and innovative learning media in the implementation of cognitive diagnostic assessment in grade IV of SD Negeri 2 Ciloa makes students less enthusiastic and focused in participating in assessment activities. The purpose of this study is to develop a Quizizz-based cognitive diagnostic assessment instrument in the Natural and Social Sciences (IPAS) subject. Researchers also want to know the level of feasibility and effectiveness of the assessment instrument developed using Quizizz media. The subjects of this study were grade IV students of SD Negeri 2 Ciloa. Students in grade IV A (experimental class) with a total of 21 students and grade IV B (control class) with a total of 22 students. The research method used Research and Development (R&D) with the ADDIE (Analyze, Design, Development, Implementation and Evaluation) development model. The feasibility test of the Quizizz-based cognitive diagnostic assessment instrument meets the very feasible category with an average of 92.38% according to media experts, validation of learning evaluations of teaching materials obtained a percentage of 86%